East African agriculture and climate change: A comprehensive analysis - Rwanda - Tenge, Ngoga G.; Alphonse, Mutabazi; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Rwanda that will appear in the peer-reviewed IFPRI monograph, East African Agriculture and Climate Change: A Comprehensive Analysis.